If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + -78 = (-10) Reorder the terms: -78 + c = (-10) -78 + c = -10 Solving -78 + c = -10 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '78' to each side of the equation. -78 + 78 + c = -10 + 78 Combine like terms: -78 + 78 = 0 0 + c = -10 + 78 c = -10 + 78 Combine like terms: -10 + 78 = 68 c = 68 Simplifying c = 68
| 9x^2=-77+18x | | x^3-10x=-3x^2-24 | | j+4=(-85) | | -87=g-92 | | 2a-3b(a-5)=5 | | w+27=(-64) | | 2/x-22=5/x-2 | | x/7-1=2 | | m-68=-48 | | -5=j+5 | | q-(-9)=73 | | 14c-7d= | | 98=-7z | | 2v-15=25 | | -15=w-62 | | 3x+14=-7+2x | | -4n=(-64) | | 10x^2+81x+8=0 | | h+(-91)=6 | | -8j=88 | | c^2-3c-85=0 | | 10x-11-8x+23=6 | | -9h=-99 | | b-(-12)=15 | | -4u-2(-u-15)=8(2u-9) | | 3=j+-9 | | 17=c-(-7) | | 6n^2+29n+28=0 | | 3Cosx=3 | | 12=-4g | | 6x-10-4x+13=-2 | | 15=s-(-4) |